2018
DOI: 10.1155/2018/2308095
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Dengue Transmission and Spatial Distribution of High Seroprevalence in Schoolchildren from the Urban Area of Medellin, Colombia

Abstract: Dengue fever is an increasing health problem in tropical and subtropical regions. During 2010 in Medellin, the younger population presented a particularly high dengue incidence rate. This study estimated dengue virus (DENV) transmission in schoolchildren (aged 5–19 years) in Medellin from 2010 to 2012. A longitudinal serological survey (IgG) and spatial analysis were conducted to determine the distribution of DENV seroprevalence. A total of 4,385 schoolchildren participated for at least one year. Dengue seropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 30 publications
0
45
0
Order By: Relevance
“…Among the various social factors, age is one of the characteristics most related to DENV infections [9,11,14,[49][50][51]. In Pernambuco, during the 3 years studied, we observed that the majority of dengue cases was reported in individuals aged between 20 and 29 and 30-39 years old.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Among the various social factors, age is one of the characteristics most related to DENV infections [9,11,14,[49][50][51]. In Pernambuco, during the 3 years studied, we observed that the majority of dengue cases was reported in individuals aged between 20 and 29 and 30-39 years old.…”
Section: Discussionmentioning
confidence: 97%
“…In different regions and in different population segments, other age groups, e.g. infants and individuals with 15-49 years, 18 years, ≥ 30 years or > 50 years, have been also related to DENV infection [9,11,14,50,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dengue is endemic in Medellin with a reported annual incidence of 161-745/100,000 and a recent epidemic in 2016 [7]. With all 4 serotypes in circulation in Antioquia, the prevalent serotypes were DENV-2 and DENV-1 in 2000-2010 [6].…”
Section: Study Site and Populationmentioning
confidence: 99%
“…In Colombia, dengue is hyper-endemic with circulation of all four serotypes, and there has been a significant increase in the number of cases of DF/severe dengue in the last 10 years, with epidemics occurring every 3-4 years [1,6]. Colombia experienced an outbreak in 2016 with 103,822 dengue cases reported [7] since a peak observed in 2013 with 65,464 lab-confirmed cases among 127,000 clinical cases [8].…”
mentioning
confidence: 99%